2017
DOI: 10.1016/j.ctro.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the IGF-1 system of cancer cells on radiation response – An in vitro study

Abstract: BackgroundOverexpression of the insulin-like growth factor-1 receptor (IGF-1R) is associated with increased cell proliferation, differentiation, transformation, and tumorigenicity. Additionally, signaling involved in the resistance of cancer cells to radiotherapy originates from IGF-1R. The purpose of this study was to investigate the role of the IGF-1 system in the radiation response and further evaluate its effect on the expression of DNA repair pathway genes.MethodsTo inhibit the IGF-1 system, we stably tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…Very few studies have been conducted on the role of IGF‐1R in resistance to radiation therapy. In multiple studies, it has been shown that suppression of IGF‐1R ROS‐mediated overactivation leads to the decreased radioresistance of different cancers both in vitro and in vivo (Denduluri et al, ; Moreno‐Acosta et al, ; Panganiban & Day, ; Venkatachalam et al, ; Yavari et al, ). In this regard, findings from Afshar () study have shown that inhibition of IGF‐1R by ectopic increase of miR‐185 suppressed radiation‐induced IGF‐1R phosphorylation/overactivation and introduced apoptosis and then radiosensitivity in CRC cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have been conducted on the role of IGF‐1R in resistance to radiation therapy. In multiple studies, it has been shown that suppression of IGF‐1R ROS‐mediated overactivation leads to the decreased radioresistance of different cancers both in vitro and in vivo (Denduluri et al, ; Moreno‐Acosta et al, ; Panganiban & Day, ; Venkatachalam et al, ; Yavari et al, ). In this regard, findings from Afshar () study have shown that inhibition of IGF‐1R by ectopic increase of miR‐185 suppressed radiation‐induced IGF‐1R phosphorylation/overactivation and introduced apoptosis and then radiosensitivity in CRC cell line.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 exerts pleiotropic effects in autocrine, paracrine, and endocrine fashions [ 2 ] by binding to its cognate IGF-1 receptors on target cells. IGF-1 signal transduction activates several downstream proteins involved in cell survival, proliferation, propagation [ 3 ], and confers radioresistance properties to tumor cells [ 4 ]. Other researchers have reported an association between aging and an increase in radiation sensitivity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the established role of IGF-1 signaling in radiation sensitivity [ 31 ], in the current report we explored the possibility of whether the link between tissue IGF-1 signaling and radiation sensitivity could be extrapolated to other animal models and if the quality and maintenance of normal IGF-1 signaling in tissues other than heart would show similarities to heart tissue. At a molecular level, we also explored the link between cardiac mitochondrial energy metabolism, cardiac antioxidant gene response mediated by Nrf2 transcription factor and their association with the radiation sensitivity.…”
Section: Discussionmentioning
confidence: 99%